2013
DOI: 10.1161/circulationaha.112.142158
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Apixaban Compared With Warfarin at Different Levels of Predicted International Normalized Ratio Control for Stroke Prevention in Atrial Fibrillation

Abstract: Fibrillation (ARISTOTLE) trial, apixaban compared with warfarin reduced stroke and systemic embolism, major bleeding, and mortality. We evaluated treatment effects in relation to 2 predictions of time in therapeutic range (TTR). Methods and Results-The trial randomized 18 201 patients with atrial fibrillation to apixaban 5 mg twice daily or warfarin for at least 12 months. For each patient, a center average TTR was estimated with the use of a linear mixed model on the basis of the real TTRs in its warfarin-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
123
2
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(150 citation statements)
references
References 25 publications
(39 reference statements)
13
123
2
9
Order By: Relevance
“…5 These findings were shown to be independent of the quality of international normalised ratio (INR) control in patients receiving warfarin. 8 …”
Section: Summary Of Phase III Noac Clinical Trials In Non-valvular Atmentioning
confidence: 99%
“…5 These findings were shown to be independent of the quality of international normalised ratio (INR) control in patients receiving warfarin. 8 …”
Section: Summary Of Phase III Noac Clinical Trials In Non-valvular Atmentioning
confidence: 99%
“…Wallentin és mtsai [19] vizsgálata szerint azoknál a betegeknél, akiknél a terápiás tartományban töltött idő 60% alatt volt, a stroke kocká-zata 2,5-szeres volt azokhoz képest, akiknek a terápiás tartományban töltött ideje 70% vagy a feletti volt, miközben a major vérzések aránya csak 2%-kal volt kisebb.…”
Section: Milyen Antitrombotikus Terápia Javasolt a Szekunder Stroke-punclassified
“…For instance, the value of TTR recorded in the centres participating in the RE-LY trial is very scattered, ranging from 44 % observed in Taiwan or India to 80 % recorded in the Sweden [2]. This point deserves attention, as the overall benefits of DOAC in terms of efficacy and safety are attenuated or lost at centres and in patients with predicted excellent INR control [13][14][15].…”
mentioning
confidence: 99%